Staging the conflicts to come; Visions of the future-tracing security practices - Junior, David Paulo Succi [UNESP]; de Castro, Helena Salim; Soares, Samuel Alves [UNESP] (Taylor & Francis, 2023)
In recent decades, the field of international security has turned its attention to practices of violence considered new, as they differ from interstate wars, such as transnational organized crime, terrorism, insurgencies and counterinsurgency, surveillance technologies and the automation of weapons and security systems, which permeated conceptions about the future of war. Despite having different natures, these phenomena have similarities, such as entailing the confrontation between state and non-state violent actors and taking place in urban environments. The present chapter explores these security dynamics, describing how they became central to contemporary international security and their potential impact on the future of warfare. This chapter focuses on Latin America, where the reduced number of interstate conflicts is contrasted with high homicide rates and the presence of organized crime, paramilitaries, militias and highly violent security forces, in a scenario of socioeconomic, gender and ethnic-racial inequalities. Finally, the chapter regards images of the future as constitutive of the present. In this sense, it argues that the way the future of war and security has been imagined is shaped and promoted by the region's highly militarized, violent and discriminatory security policies.